Биологические основы динамики численности непарного шелкопряда (Porthetria dispar L.). Сообщение I. Плодовитость - Колыбин, В.А.; Киреева, И.М.; Зелинская, Л.М. (Вестник зоологии, 1974)
The Porthetria dispar L. ability to reproduction is not the same under different landscape-climatic conditions and at different stages of gradation. Physiological peculiarities of the insect organism determine the potential fecundity and are the basis which reflects the regulating affect of the environment factors. The real fecundity, being a basis of the species number in the given territory, is only a derivative of the combined effect of internal and external factors determining the insect development.